Aligning Work Practices, Mobile Technology and Strategy for Performance Improvement: The Case of SMEs in Uganda. Issue 1 (5th December 2017) - Muhanguzi, Samuel; Kyobe, Michael
Abstract: Small and Medium Enterprises (SMEs) contribute to economic development. However, their competitiveness is threatened by globalization and poor work practices. While mobile technology can address work practice challenges in SMEs, this technology has not been effectively leveraged by SMEs and little is still known about how best SMEs can match mobile technology applications with work practices and business strategy to enhance performance. The objective of this study was to identify combinations of these elements that provide better performance in SMEs in a developing nation. To achieve this objective the perspective of alignment as Gestalts was adopted. A survey was conducted in 174 SMEs in Uganda, followed by some interviews. Quantitative and qualitative techniques were then used to analyse the findings. High performers align ordinary mobile technology applications to strategies that improve customer services and productivity in order to optimise work practices across different stages of their business activities.